#Online harms or benefits? An ethnographic analysis of the positives and negatives of peer‐support around self‐harm on social media. (27th May 2020) - Lavis, Anna; Winter, Rachel
Abstract : Background: There is emerging evidence of the potentially detrimental impact of social media on young people's mental health. Against this background, online self‐harm content has been a recent focus of concern across academia, policy and the media. It has been argued to encourage or even cause acts such as self‐cutting through mechanisms of contagion. However, little is known about why a young person might engage with such content or about its impact on behaviour or well‐being. Methods: Online ethnographic observation of interactions around self‐harm on Twitter, Reddit and Instagram : collection and analysis of 10, 169 original posts and 36, 934 comments, both written and pictorial, at two time‐points in 2018 and 2019. Ten in‐depth semi‐structured interviews exploring engagements with self‐harm content on social media. Results: Our data show that peer support is the central component of online interactions around self‐harm. Young people accessing such content are likely to already be self‐harming; they may turn to social media to understand, and seek help for,  their actions and feelings in a context of offline stigma and service support gaps. This paper engages with the mechanisms, complexities and impact of this peer‐support, reflecting on the benefits and dangers to caring for oneself and others through social media. Conclusions: Self‐harm content is a fraught issue at the centre of current debates around risks and opportunities for child and adolescent mental health in the digital age. Whilst the importance of supporting young people's online safety is clear, moves to eradicate self‐harm content must be undertaken with caution so as not to cause unintentional harm. Our research highlights a need to think beyond a model of contagion, instead attending to other mechanisms of harm and benefit. In so doing, it challenges prevailing attitudes towards online communication about self‐harm and accepted approaches to managing this.